Phytochemical composition and antioxidant activity of peach as affected by pasteurization and storage duration - Oliveira, Ana (2013)
Fruit are very perishable and are often preserved as heat-processed foods. Clingstone peach [Prunus persica (L.) Batsch ‘Catherine’] fruit were heat-treated at 90 C for 5 min and stored under aseptic conditions at room temperature (ca. 22 C) for 90 days. Significant reductions in total carotenoids were observed immediately after pasteurization but total antioxidant activity and the concentration of total phenolics were unaffected. Pasteurization induced significant reductions in the concentration of protocatechuic acid (from 10.2 to 5.8 mg/g fw), zexanthin and b-cryptoxanthin. Significant reduction in antioxidant activity, expressed as ascorbic acid equivalents, from 0.52 to 0.25 mg/g fw, was observed during storage of pasteurized peach for 90 days. Total phenolics, expressed as gallic acid equivalents, decreased during storage from 0.57 to 0.28 mg/g fw and total carotenoids decreased from 4.0 to 1.3 mg/g fw. Procyanidin B1 increased from 15.8 to 26.8 mg/g fw and chlorogenic acid and neochlorogenic acid increased 35 and 43%, respectively. ( )-Epicatechin decreased during storage from 13.1 to 4.0 mg/g fw and quercetin- 3-glucoside from 7.3 to 4.4 mg/g fw. All carotenoids decrease significantly with the exception of zeaxanthin, which increased during storage. Storage duration strongly affected the concentration of phenolics and carotenoids in pasteurized peach.